Bone-Anchored Titanium Implants in Patients with Auricular Defects: Three Years and 27 Patients' Experience - Mevio, Emilio (Int J Otolaryngol, 2016)
Different surgical solutions have been proposed for reconstruction of the auricle following loss of the pinna through traumatic injury or neoplastic disease or in patients with congenital defects. Surgical treatment may involve the insertion of an autogenous rib cartilage framework or the use of a porous polymer material inserted into an expanded postauricular flap. Reconstruction with rib cartilage has yielded good results but requires more than one surgical step, and adverse events can occur both at the donor and at the acceptor site; cases of prosthesis rejection have also been described following application of the polymeric prosthesis. The use of a titanium, dowel-retained silicone prosthetic pinna, fixed to the temporal bone, has recently been proposed. This useful surgical approach is indicated particularly after resection of the pinna caused by neoplastic disease or in traumatic auricular injury. Osseointegrated titanium implants used in 27 patients in this study provided them with a safe, reliable, adhesive-free method of anchoring the auricular prostheses. The prostheses allowed recovery of normal physical appearance and all the patients reported that they were completely satisfied with the outcome of the surgical reconstruction. No surgical complications, implant failures, or prosthetic failures were encountered over six months to three years.